2013
DOI: 10.4012/dmj.2012-266
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dental porcelain containing silver nanoparticles on static fatigue

Abstract: The purpose of this study was to clarify the effect of silver nanoparticles on the behavior of subcritical crack growth (SCG) in dental porcelains. Prior to occurrence of fast fracture in dental porcelains, SCG occurs and leads to strength degradation over time. SCG in dental porcelains can be characterized by the stress corrosion susceptibility coefficient, n. A higher n value means a higher resistance to SCG. In this study, porcelain disks were prepared by mixing a commercial dental porcelain powder with dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…It was confirmed that AgNPs significantly improved the Young’s modulus and fracture toughness of dental porcelain and reduced the risk of fracture of porcelain restorations. 131 , 132 …”
Section: Antimicrobial Agbms Incorporated In Dental Materialsmentioning
confidence: 99%
“…It was confirmed that AgNPs significantly improved the Young’s modulus and fracture toughness of dental porcelain and reduced the risk of fracture of porcelain restorations. 131 , 132 …”
Section: Antimicrobial Agbms Incorporated In Dental Materialsmentioning
confidence: 99%
“…Subcritical crack growth occurs and leads to strength degradation over time. It was shown that addition of AgNPs significantly increased the stress corrosion susceptibility coefficient of dental porcelain [1].…”
Section: Since 2002mentioning
confidence: 99%
“…Optimal optical and biological properties of dental porcelains make them the first selection for both dentists and patients. However, a hard brittle porcelain will be cracked or damage when surface comes under a significant load or impact, enhancement of strength and fracture toughness of dental porcelain through different modification methods have been recommended and one of these methods is the addition of ductile metal particles [1].…”
Section: Introductionmentioning
confidence: 99%
“…The idea is to improve fracture toughness and prevention of crack propagation. One of the studies revealed that AgNPs increase the fatigue parameter, shorten the time required for slow crack growth and reduce crack growth rate [145]. Fujieda et al proved that fracture toughness and Young's modulus increased with addition of AgNPs and Pt-NPs [146].…”
Section: Prostheticmentioning
confidence: 99%